Failure of society and revenge of its member / Muhammad Danyal Khan - Khan, Muhammad Danyal (2014)
Man is a being with feelings which are controlled by the external environment. Born in society, man is in chains of rights and duties. Being part of the society, humans perform their duties for the welfare of society and what they get back in the shape of right is protection from the society in rem. Now, the act of ending one's life is deemed as coward act of a person but if we look the idea of suicide in the prism of social contract, it bears different rationale. The duty of a human to become the beneficial part of society is correlated by the right of protection of human. This protection can be in the shape of economy, security and other social needs etc. In my point of view, suicide is nothing but the failure of providence of right to the person committing suicide. It is a revenge taken by the suicide committing person from the society when it fails to perform its function to protect its part in one way or another. So, the person committing suicide makes the mind that if the society does not pays back his welfare against his or her positive part played in society than it should suffer in the shape of his absence from the society. Suicide is not only a cowardice act of a person but also is failure of society at large. This paper will make the sense of suicide in the wake of society's duty to provide a shelter to its member. Relation of society with its member in the shape of human will be studied and special focus will be given to situation in Pakistan.